Long-Term Outcome after Asphyxia and Therapeutic Hypothermia in Late Preterm Infants: A Pilot Study - Hanne Lademann (Healthcare, 2021)
Therapeutic hypothermia (THT) is the recommended treatment for neuroprotection in (near) term newborns that experience perinatal asphyxia with hypoxic-ischemic encephalopathy. The benefit of THT in preterm newborns is unknown. This pilot study aims to investigate long-term outcomes of late preterm asphyctic infants with and without THT compared to term infants. The single-center, retrospective analysis examined medical charts of infants with perinatal asphyxia born between 2008 and 2015. Long-term outcome was assessed using the Bayley Scales of Infant Development 2 at the age of (corrected) 24 months. Term (n = 31) and preterm (n = 8) infants with THT showed no differences regarding their long-term outcomes of psychomotor development (Psychomotor Developmental Index 101 ± 16 vs. 105 ± 11, p = 0.570), whereas preterm infants had a better mental outcome (Mental Developmental Index 105 ± 13 vs. 93 ± 18, p = 0.048). Preterm infants with and without (n = 69) THT showed a similar mental and psychomotor development (Mental Developmental Index 105 ± 13 vs. 96 ± 20, p = 0.527; Psychomotor Developmental Index 105 ± 11 vs. 105 ± 15, p = 0.927). The study highlights the importance of studying THT in asphyctic preterm infants. However, this study shows limitations and should not be used as a basis for decision-making in the clinical context. Results of a multicenter trial of THT for preterm infants (ID No.: CN-01540535) have to be awaited.